1, (-4)3
(-4).(-4). (-4).(-4)
2, -52
-5 . -5
3, (2/3)2
(2/3) . (2/3)
4, (2/3)2
(2/3) . (2/3)
5, (-3)4
(-3) . (-3) . (-3) . (-3)
So do my answers to this questions seem correct?
First, you won't be "solving". To "solve" means to find the value of a pronumeral.
You will be "simplifying".
Anyway...
1. $\displaystyle (-4)^3 = (-4)\cdot(-4)\cdot(-4)$
$\displaystyle = -64$.
2. $\displaystyle (-5)^2 = (-5)\cdot(-5)$
$\displaystyle = 25$
3. $\displaystyle \left(\frac{2}{3}\right)^2 = \frac{2^2}{3^2}$
$\displaystyle = \frac{4}{9}$
4. It appears that Q. 4 is the same as Q. 3.
5. $\displaystyle (-3)^4 = (-3)\cdot(-3)\cdot(-3)\cdot(-3)$
$\displaystyle = 81$.